Electrophoretically Deposited Green Synthesized Silver Nanoparticles Anchored in Reduced Graphene Oxide Composite Based Electrochemical Sensor for Detection of Bisphenol A. Issue 9 (6th September 2021) - Verma, Damini; Dhiman, Tarun Kumar; Das Mukherjee, Maumita; Solanki, Pratima R.
Abstract : Bisphenol A (BPA), an endocrine-disrupting compound, is used in beverage and food packaging, leaches into the water and food source cycles affecting humans and the environment due to the thermodynamic instability of BPA. Herein, we report a sensitive, quick, economical, simple, and selective electrochemical platform exploring green synthesized silver nanoparticles (AgNps) anchored in reduced graphene oxide (RGO) composite for BPA determination in milk and water samples. For confirmation of the synthesis of AgNps-RGO composite, characterizations were done with X-ray diffraction, UV–visible spectroscopy, Raman spectroscopy, high-resolution transmission electron microscopy, and scanning electron microscopy. The sensor platform was fabricated using indium tin oxide (ITO) glass substrate through electrophoretic deposition. The sensor electrode (AgNps-RGO/ITO) achieved a sensitivity of 2.56 μ A (log μ M) −1 cm −2, a detection limit of 0.14 μ M, and linear response in the range of 1.9 × 10 −10 to 0.820 μ M. This is mainly ascribed to the synergetic benefits of AgNps and RGO, which are synthesized in situ through the green route using Cinnamomum tamala leaf extract. The sensor showed insignificant interference from its analogs, inorganic and organic species, along with good repeatability and reproducibility. The developed sensor demonstrated good potential application to detect BPA with acceptable recoveries and their relative standard deviation values.